ANALISIS TERHADAP KEWENANGAN MAHKAMAH KONSTITUSI DALAM PENYELESAIAN SENGKETA KEWENANGAN LEMBAGA NEGARA BERDASARKAN UNDANG-UNDANG DASAR NEGERA REPUBLIK INDONESIA TAHUN 1945 - Fira Natasha; Ridham Priskap (Universitas Jambi, Fakultas Hukum, 2021)
The presence of the Constitutional Court is one of the demands of the state administration, changes in the state administration of the Republic of Indonesia after the amendment. The Constitutional Court has an important authority, one of the powers of the Constitutional Court is to resolve disputes over authority between state institutions. Disputes on authority between state institutions are possible because of the implementation of a system of checks and balances in the Indonesian constitutional system as a consequence of the separation of powers as regulated in the 1945 Constitution of the Republic of Indonesia on state institutions. In view of the Constitution of the Republic of Indonesia and Law Number 24 of 2003 in conjunction with Law Number 8 of 2011 concerning the Constitutional Court, they do not explain in detail the implementation of this authority. For this reason, it is necessary to conduct research on the analysis of the authority of the Constitutional Court in resolving disputes over the authority of state institutions based on the 1945 Constitution of the Republic of Indonesia. Keywords: Authority of the Constitutional Court, Disputes on Authority of State Institutions. Kehdiran Mahkamah Konstitusi salah satunya merupakan tuntutan ketatanegaraan, perubahan ketatanegaraan Republik Indonesia setelah amandemen. Mahkamah Konstitusi memiliki kewenangan yang penting, salah satu kewenangan Mahkamah Konstitusi adalah menyelesaikan sengketa kewenangan antar lembaga negara. Sengketa kewenangan antar lembaga negara dimungkinkan terjadi karena diterapkannya sistem checks and balances dalam sistem ketatanegaraan Indonesia sebagai konsekuensi adanya pemisahan kekuasaan sebagaimana diatur dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 terhadap kelembagaan negara. Mengingat Undang-Undang Dasar Negara Republik Indonesia maupun Undang-Undang Nomor 24 Tahun 2003 jo Undang-Undang Nomor 8 Tahun 2011 tentang Mahkamah Konstitusi tidak menjelaskan secara detail pelaksanaa kewenangan tersebut. Untuk itu perlu dilaksanakan penelitian mengenai analisi terhadap kewenangan Mahkamah Konstitusi dalam penyelesaian sengketa kewenangan lembaga negara berdasarkan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Kata Kunci : Kewenangan Mahkamah Konstitusi, Sengketa Kewenangan Lembaga negara.